Competitive interaction between airports, airlines and high-speed rail: Summary and conclusions - OECD; International Transport Forum (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
This paper summarizes, structures, and provides some context for discussions of the Round Table mentioned in the title. The first part of the paper focuses on sources of market power for airports and on policy responses. When an airport is congested and competition with other airports is limited, regulation may be justified, and the dual till approach likely works best. In other cases, however, policy should establish conditions for competition to emerge as much as possible, instead of attempting to design a general regulatory framework. The second part of the paper discusses elements of climate change policy in aviation. Including aviation in emission trading schemes is a sensible idea, but should not be expected to produce major cuts in CO2 emissions from aviation; containing its growth possibly is a more realistic, yet ambitious and not necessarily socially optimal, objective. High-speed rail is justified in some situations, but is not a general alternative for air travel and certainly not a second-best way to reduce greenhouse gas emissions from aviation.
Keywords: 330; Verkehrsträgerwettbewerb; Flughafen; Luftverkehrsgesellschaft; Hochgeschwindigkeitszug; Welt